Financial, business and trust cycles: the issues of synchronization - Yuriy Bilan; Maryna Brychko; Anna Buriak; Tetyana Vasilyeva (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu, 2019)
Starting from 1920, the growing body of research has been focused on the role of psychological factors in cycle theories. Mainstream macroeconomic models are insufficient for exploring interaction among economic agents, financial institutions, and the real sector of economy. This paper is among the first to show the synchronization of financial and business cycles through the trust cycle but with a certain delay in terms. The paper presents the conceptualization of trust as a combination of two pillars – structure-based confidence based on objective information about system competences, regulations, and norms, and sentiment-driven actions of economic agents (feelings, emotions, and other subjective characteristics). The paper offers a theoretical descriptive model of a trust cycle that allows exploring several stages of correlation between financial fluctuations, trust changes, and large swings in business cycle.